Encapsulation of fish oil with N-stearoyl O-butylglyceryl chitosan using membrane and ultrasonic emulsification processes. (5th June 2015) - Chatterjee, Sudipta; Judeh, Zaher M.A.
Highlights: Fish oil was encapsulated using hydrophobic N -stearoyl O -butylglyceryl chitosan. Microencapsulation using membrane & ultrasonic emulsifications were compared. Microcapsules showed sustained release oil and profile depended on the process. Encapsulation impeded heat transfer and increased thermal stability of the fish oil. Abstract: Fish oil-loaded microcapsules were prepared from oil-in-water emulsions using N -stearoyl O -butylglyceryl chitosan as shell material. The emulsions were prepared by both membrane and ultrasonic emulsification processes under variable conditions to examine the effect of the emulsification process and encapsulation conditions on the characteristics of the microcapsules. The microcapsules were characterized with respect to their morphologies, colloidal stability, loading capacity, encapsulation efficiency and release profile. The microcapsules formed by the membrane emulsification process exhibited larger diameter compared to those from the ultrasonic emulsification process which gave a mean effective diameter of ≈1 μm. The microcapsules obtained by membrane emulsification process gave better loading capacity and encapsulation efficiency. The microcapsules from both processes showed sustained release of fish oil and the release profile depended on the type of the process. TGA confirmed that encapsulation using N -stearoyl O -butylglyceryl chitosan impeded heat transfer and significantly increased the thermal stability of the encapsulated fish oil.